2021
DOI: 10.1038/s41598-021-96959-4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of sex difference in circulating uric acid is associated with higher testosterone and lower sex hormone-binding globulin in adolescent boys

Abstract: Men have higher circulating levels of uric acid than women. This sex difference is suspected to be a result of suppressive effects of estradiol on uric acid. If so, estradiol would be inversely associated with circulating uric acid. This study aimed to test this hypothesis. This cross-sectional study included 9472 participants (weighted sample size of 184,342,210) aged 12–80 years from the 2013 to 2016 US National Health and Nutrition Examination Survey. Associations of sex hormones with uric acid were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 38 publications
2
24
1
Order By: Relevance
“…Experts suspected that the lower reference value of SUA in women might be related to estrogen inhibiting xanthine oxidase that produces UA (35,36). However, a large representative cohort study in the US found that gender differences in UA levels are formed during adolescence (37). However, our study found that SUA levels were more likely to be affected by total CA levels in adolescent girls than boys.…”
Section: Discussioncontrasting
confidence: 72%
“…Experts suspected that the lower reference value of SUA in women might be related to estrogen inhibiting xanthine oxidase that produces UA (35,36). However, a large representative cohort study in the US found that gender differences in UA levels are formed during adolescence (37). However, our study found that SUA levels were more likely to be affected by total CA levels in adolescent girls than boys.…”
Section: Discussioncontrasting
confidence: 72%
“…4 D). These findings are in agreement with a recent study where higher testosterone was associated with an increment in uric acid levels in adolescent boys 34 , 35 , and a case report of hypogonadism where renal function decreased after testosterone replacement therapy and creatinine levels increased 36 . However, considering that creatinine is also involved in muscle metabolism, the positive correlation between testosterone and creatinine might reflect the increase in muscle mass and not an impairment in renal function 37 .…”
Section: Discussionsupporting
confidence: 93%
“…Sex hormones could be part of the differences between genders due to their effect on circulating uric acid, eGFR level, and muscle strength. During adolescence, higher testosterone and lower sex hormone-binding globulin were reported as the gender difference in circulating uric acid [29].…”
Section: Discussionmentioning
confidence: 99%